(untitled) (Fiep Bulletin - online, 2015)
The aim of the present study is to verify the degree of contraction of the pelvic floor musculature with women aged between 20 to 30 years old, who have already practiced weightlifting for at least one year and to compare the subjective evaluation (functional) with the objective evaluation (perineometer). Ten women were evaluated by perineometry, and by functional evaluation by writing down the maximum amount of contraction. The parametric and paired t-test was used to compare the same group of women among the functional evaluation and the perineometer test, and also the Pearson correlation test, analyzing the correlation between the functional test and the perineometer test with height, weight, age and the practice of perineal exercises. There was statically difference between the two evaluations, obtained by the rating of p which was equal to p=0.0011, the difference presented statistically was significant (p<0.05). It can furthermore be noted that with the correlation analyzes among the women who were evaluated there was not influence of weight (r=0.2/ P=0.57) in the functional and perineometer evaluation (r=0.45/ P=0.18) nor of height (r= -0.33/ p=0.36) functional and perineometer evaluation (r=0,31/ p=0,39). The age (r=0.14 / p=0.70) in the functional and perineometer evaluation (r= 0.04 / p=0.92). It is concluded that the practice of weight training does not have correlation to growth of strength in the pelvic floor musculature. When comparing both methods to evaluate the strength of the pelvic floor, the perineometer test turned out to be more reliable than the subjective method. It is believed that this study will help in the actions, strategies and future intervention related to health promotion and prevention of diseases related to the pelvic floor in women.